Frontispiece. Issue 8 (9th August 2013) - Unknown
<x xml:space="preserve">Abstract</x> The frontispiece shows an integration of the siloxane formation reactions of both the nonhydrolytic sol–gel (NHSG) process and Piers–Rubinsztajn reaction as "Lewis acid promoted siloxane syntheses without involving silanol groups". The Minireview by R. Wakabayashi and K. Kuroda on page 764 ff. shows that both reactions are quite similar, thus the research should be merged and the knowledge shared. The combined view of the NHSG and Piers–Rubinsztajn reaction should realize a more sophisticated molecular design of siloxane compounds, which surely contributes to the development of advanced functional materials.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>